2001
DOI: 10.1007/s002100100412
|View full text |Cite
|
Sign up to set email alerts
|

Species- and agonist-dependent differences in the deactivation-kinetics of P2X 7 receptors

Abstract: In this study we have expressed recombinant P2X7 receptors in HEK293 cells and examined the reasons for the species- and agonist-dependent differences in the time taken for the closure of the P2X7 receptor ion-channels after agonist removal. Channel closure times, measured in electrophysiological studies or by measuring cellular permeability to ethidium cations, were slower at rat than at human or mouse P2X7 channels following washout of the P2X7 agonist 2'- and 3'-O-(4-benzoylbenzoyl)-ATP (BzATP). In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Here, we compared the Yo-Pro-1 uptake capacity of murine and humanized P2X7R endogenously expressed in primary cells obtained from respective mice. The detected difference in Yo-Pro-1 uptake between humanized and mouse P2X7R was comparable to previous reports [8]. To activate the pore formation via the murine P2X7R to levels comparable with the human P2X7R ~10 times higher BzATP concentrations were required.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Here, we compared the Yo-Pro-1 uptake capacity of murine and humanized P2X7R endogenously expressed in primary cells obtained from respective mice. The detected difference in Yo-Pro-1 uptake between humanized and mouse P2X7R was comparable to previous reports [8]. To activate the pore formation via the murine P2X7R to levels comparable with the human P2X7R ~10 times higher BzATP concentrations were required.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we observed that the modulator TFP had a potentiating effect on Yo-Pro-1 uptake exclusively on the murine receptor but not on the humanized P2X7R. Species-specific effects of positive and negative modulators have repeatedly been described for P2X7R orthologs [8, 10, 57, 58]. These findings suggest that our humanized mouse model is well-suited to discriminate properties of mouse and human P2X7R orthologs in an in vivo context and thereby opens new possibilities for the screening and evaluation of new P2X7R agonists and antagonists.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A brain infusion cannula was bilaterally implanted in the hippocampus (AP = −3.8, ML = ±3 mm, DV = 3.5 mm, 1 μl, 0.5 μl min −1 ). Seven days after implantation, vehicle, ATP (100 nM), BzATP (10.5 nM), BBG (Brilliant Blue G, one of the safest dyes currently used, is a well-known P2X7 receptor antagonist,1 pM), or A438079 (a selective competitive antagonist for the human and rodent P2X7 receptor with good bioavailability and CNS penetration widely used in animal models of disease, 1.75 nM) was delivered into the hippocampus of free-moving rats for 21 days [3949]. The behavioral test was conducted before the infusion on the first day and 30 min following the infusion on the 21th day.…”
Section: Methodsmentioning
confidence: 99%